La discriminación estructural hacia las mujeres como nexo de la reparación transformadora: análisis de las sentencias n.° 3-19-JP/20 y Acumulados y n.° 202-19-JH/21 (Tema Central) - Paula Aguirre, Christian Alexander (2022)
This paper aims to compare the concepts of integral and transformative reparation in cases of structural discrimination based on a comparative analysis of Judgments No. 3-19-JP/20 and Accumulated and No. 202-19-JH/21 by the Constitutional Court of Ecuador. In carrying out this reflection, a qualitative methodology was applied from documentary analysis techniques. The selected judgments show structural discrimination that women experience in their daily life due to a patriarchal system of society, but that constitutional law has the potential to modify through the development of appropriate reparation measures. This approach deepens material equality as it aims to develop reparations as the governing principle to be developed in reparation measures for historically discriminated groups, who live in situations of exclusion that affect them systematically and historically. This keeps them subordinated and oppressed by society and thus provokes structural discrimination. This calls for state recognition of this discrimination and a state obligation to reverse or modify this oppressive structure. Thus, it is concluded that the transformative reparation measures allow solving problems of structural discrimination, which is what the integral reparation approach is aiming at. For this reason, an expansion of the conception of reparation in cases of structural discrimination is required.